Genetic Heterogeneity in Bartter Syndrome: Clinical and Practical Importance - Florea, Laura; Caba, Lavinia; Gorduza, Eusebiu Vlad (Frontiers in Pediatrics, 2022)
1 Bartter syndrome (BS) is a rare tubulopathy that produced polyuria, hypokalemia, hypochloremic metabolic alkalosis, normotensive hyperreninemic hyperaldosteronism. It is characterized by locus, clinical and allelic heterogeneity. Types 1-4 Bartter Syndrome are inherited according to an autosomal recessive pattern, while type 5, which is transient, is X linked. There are specific correlations between the clinical expression and the molecular defect, but being a rare disease such studies are rare. Therapeutic interventions are different, being correlated with types of Bartter Syndrome.